Disposing of the Joint Parts of the Building and the Land Needed for its Use by the Future Condominium Owners in Favor of the Investor when Concluding Purchase and Sales Agreement - Midorović, Sloboda D; Cvetić, Radenka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
At the outset the paper gives an overview of the property entitlements of the condominium owners over joint parts of the building and the land needed for the use thereof, so as to examine the legal regime of these accessory rights. Furtheron, the typical contractual clauses by which the buyers of the specific parts of a building under construction waive their entitlements to use and dispose of some joint parts of the building and some parts of the land plot in favour of investor, despite the fact that these entitlements are mandatorily attached to the status of condominium owners. The wide spectrum of „disspossession“ of entitlements  of condominium owners has been detected contrary to the legal rules which guarantee them the right to administer and decide over accessory rights within the residential community in the proceedings prescribed by law. Numerous questions that arise with regard to such a contractual practice have been opened, while the answers thereto are given by way of systematic interpretation of the pertinent legal rules. This is followed by the analyses of the notary public practice with regard to these contractual clauses, in that it was examined how the notaries public warn the contractual parties on the validity of such clauses. Connected therewith, vast discrepancies have been uncovered, while singling out the example of best notary public practice, which shall be followed. Upon the legal analyses, the authors have taken the stance on the invalidity of such contractual clauses along with the consequences thereof with respect to the contract as a whole. This conclusion has been based on the previous establishment that all the preconditions for the application of the institute of the partial nullity of the contract have been met.
Keywords: accessory rights of condominium owners, contractual clauses on waiving or limiting the accessory rights, investor, warning of the notary public while solemnizing the contract, partial nullity of the contract